Comparison of Seminal Superoxide Dismutase (SOD) Activity Between Elite Athletes, Active and Non Active Men - Tartibian, Bakhtyar; Maleki, Behzad Hajizadeh; Abbasi, Asghar; Eghbali, Mehdi; Asri-Rezaei, Siamak; Northoff, Hinnak (IntechOpen, 2012)
None